Effects of oxidation and inter-diffusion on the fracture mechanisms of Cr-coated Zry-4 alloys: An in situ three-point bending study. (15th December 2021) - Jiang, Jishen; Du, Mingyue; Pan, Ziyan; Yuan, Mingduo; Ma, Xianfeng; Wang, Biao
Graphical abstract: Highlights: Different cracking modes of pre-oxidised and vacuum-annealed Cr coatings were studied. Crack resistance of Cr coating was greatly enhanced due to recrystallization effect. The brittle diffusion layer was easier to generate micro-cracks under external loadings. Oxygen transportation, inter-diffusion and phase transformation led to pre-failure of Cr coatings. Abstract: Chromium (Cr)-coated zirconium alloys have been considered as a promising candidate material for accident-tolerant fuel (ATF) cladding for nuclear reactors because of their superior oxidation resistance under accident conditions. However, the oxidation and diffusion behaviours that occur in the Cr coating–Zr substrate system at high temperatures significantly affect the microstructure and mechanical properties of the coating, leading to cracking modes that are distinct from those of the as-deposited coating. To understand the effects of oxidation and inter-diffusion on the fracture mechanisms of Cr-coated Zry-4 alloys, in situ three-point bending tests were conducted in this study. Crack initiation and propagation in the oxidised and vacuum-annealed coatings were observed in real time. The results showed that high-temperature exposure led to recrystallisation of the Cr coating (columnar grains transformed into equiaxed grains), which greatly enhanced the crack resistance of the Cr coating. However, a diffusion-induced intermetallic ZrCr2 layer and an α-Zr(O) layer (which transformed from β-Zr owing to oxygen transportation) formed simultaneously at the coating/substrate interface. The micro-cracks formed in these brittle layers rapidly penetrated all the layers under external load, leading to premature failure of the coated sample.